Dietary phytochemical index and the risk of non-alcoholic fatty liver disease: A case-control study among Iranian adults - Ammar Salehi-sahlabadi; Farshad Teymoori; Ebrahim Mokhtari; Maryam Taghiyar; Azita Hekmatdoost; Parvin Mirmiran (Elsevier, 2022)
Backgrounds: Dietary phytochemical index (DPI) is an inexpensive method for estimating the amounts of phytochemicals in foods. No study has investigated the association between DPI and non-alcoholic fatty liver disease (NAFLD). Our study aimed to compare DPI in patients with NAFLD and the control group. Methods: This is a case-control study of 250 subjects with NAFLD and 450 healthy subjects attending the Metabolic Liver Disease Research Center as a referral center affiliated to Isfahan University of Medical Sciences. DPI was calculated based on data collected from a 168-item validated food frequency questionnaire. Sociodemographic data, physical activity, and anthropometric measures such as body weight, height, and waist circumference were determined. Results: In the final adjusted model, the odds ratio (OR) of NAFLD across the DPI tertiles decreased significantly (OR = 0.55, 95 %CI = 0.31-0.95) (P-trend = 0.03). The highest vs. lowest tertiles of vegetable and olives PI were significantly associated with a lower risk of NAFLD (OR and 95 % CI = 0.26 (0.14-0.47); OR and 95 % CI = 0.51 (0.29-0.90), p for trend < 0.001, respectively), however, there was no significant relation between other PI components and NAFLD. Conclusion: This case-control study suggested that a higher PI score is associated with a reduced chance of NAFLD after adjusting for confounding variables. In addition, the highest tertile of vegetable and olives PI was significantly associated with a lower risk of NAFLD.